2022
DOI: 10.20517/mtod.2022.15
|View full text |Cite
|
Sign up to set email alerts
|

MAFLD under the lens: the role of gut microbiota

Abstract: Obesity, the metabolic syndrome, and metabolic dysfunction-associated fatty liver disease (MAFLD) can be portrayed as transmissible diseases. Indeed, they can be induced, in animal models, by cohabitation or by transplantation of fecal microbiota from other animals or humans with those diseases. As such, to get a 10,000-foot view, we need to see under the lens the microbes that populate our gut. Gut microbiota participates in the harvesting of energy from nutrients, it allows the digestion of otherwise indiges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 176 publications
0
1
0
Order By: Relevance
“…Women appear to be particularly susceptible to MAFLD after menopause, when there is a rise in cardiometabolic risk factors and the prevalence of MAFLD increases. However, if a younger woman has MAFLD, her risk of heart failure is much higher as reported recently by Wu et al, who found in a prospective cohort study that the risk of heart failure is greater in young women with MAFLD ( age < 45 years) compared to men [54] . Instead of being an "innocent" bystander with fat accumulation in the liver, MAFLD is emerging as an important CVD risk marker that could be a therapeutic target.…”
Section: Metabolic Associated Fatty Liver Diseasementioning
confidence: 57%
“…Women appear to be particularly susceptible to MAFLD after menopause, when there is a rise in cardiometabolic risk factors and the prevalence of MAFLD increases. However, if a younger woman has MAFLD, her risk of heart failure is much higher as reported recently by Wu et al, who found in a prospective cohort study that the risk of heart failure is greater in young women with MAFLD ( age < 45 years) compared to men [54] . Instead of being an "innocent" bystander with fat accumulation in the liver, MAFLD is emerging as an important CVD risk marker that could be a therapeutic target.…”
Section: Metabolic Associated Fatty Liver Diseasementioning
confidence: 57%